Empirical correlation between uncorrected standard penetration resistance (N) and shear wave velocity (VS) for Kathmandu Valley, Nepal - Dipendra Gautam (Geomatics, Natural Hazards & Risk, 2017)
The indirect method of estimation of VS is more important as geophysical tests associated with direct determination of VS are not feasible in developing countries like Nepal; on the contrary, standard penetration resistance (SPT-N) measurement is practised widely for building constructions even in residential buildings these days. Good SPT-N database is nowadays available so that eventual development of correlation between these two parameters may provide a strong basis of site characterization as the average shear wave velocity (VS, 30) of the upper 30-m soil layer is an important parameter for site characterization. Historically, Kathmandu Valley has experienced anomalous earthquake damage especially at locations with alluvial cover and site characterization is must for improving seismic design considerations. In order to depict a correlation between shear wave velocity and standard penetration resistance available 500 secondary data pairs are used and formulations are obtained considering the geological and geotechnical characteristics. Separate correlations for shear wave velocity as a function of uncorrected standard penetration resistance are developed for all soils, sands and clays separately. Correlation developed for Kathmandu Valley shows significant acquaintance with the existing correlations across the world developed for all soils, sands and clays.